Public participation in genetic databases: crossing the boundaries between biobanks and forensic DNA databases through the principle of solidarity - Machado, H (2015)
The ethical aspects of biobanks and forensic DNA databases are often treated as separate issues. As a reflection of this, public participation, or the involvement of citizens in genetic databases, has been approached differently in the fields of forensics and medicine. This paper aims to cross the boundaries between medicine and forensics by exploring the flows between the ethical issues presented in the two domains and the subsequent conceptualisation of public trust and legitimisation. We propose to introduce the concept of ‘solidarity’, traditionally applied only to medical and research biobanks, into a consideration of public engagement in medicine and forensics. Inclusion of a solidarity-based framework, in both medical biobanks and forensic DNA databases, raises new questions that should be included in the ethical debate, in relation to both health services/medical research and activities associated with the criminal justice system.